Peculiarities of the research field of Old Prussian proper names: principles of naming determined by time, place, language and history - Blažienė, Grasilda (Baltistica, 2023)
Old Prussian proper names are neither timeless nor spaceless. In the 2nd century CE, the Greek Claudius Ptolemy mentioned the names of two Prussian tribes, Γαλίνδαι καὶ Σουδινοί (Geogr.3,5,9), in the space of Tacitus. The records and mentions of proper names mark an important spiritual and cultural process revealing that proper names are not only related to the history of language but also to the history of society. Researchers of Old Prussian proper names and other interested parties directed their look towards a multitude of manuscript documents, the writing of which began in the 13th century and was intensively continued hereafter. The search undertaken by linguists, onomasticians, historians, geographers, ethnographers and scholars from other fields as well as enthusiastic amateurs interested in Old Prussian was not only driven by Old Prussians but also by the Teutonic Order and its scribes, who recorded the data relating to Old Prussian proper names as they heard them from informants. As the onomastic material is piling up, we start considering how to make it accessible not only to linguistic but also to socio-onomastic interpretation and what connection can be established between name-givers and name-recipients (if we consider not only people but also the names of settlements and all other places that surrounded the Old Prussians of Sambia). Further studies are difficult and sometimes even impossible without investigating the context in which the proper name was written down, i.e., without detailed documents, whether they are handwritten or printed. The article discusses several Sambian anthroponyms and oikonyms naming the non-surviving settlements, which were mentioned in historical sources one or several times, as well as the oikonyms of later periods, which were found, revised and essentially supplemented by the author and to which attention has not yet been drawn, even though they are possibly of Prussian origin. The author has already discussed them in previous works, but in the light of new facts, a fresh perspective is required.